Di Balik Panggung Reforma Agraria: Perjuangan Tersembunyi Perempuan Tani - Pinky Chrysantini (Antropologi Indonesia, 2010)
Women often considered as ‘non-actor’ in the struggle to get access to land and its utilization. The lack of peasant women’s role in the land reform can be seen as cultural limitation of the land tenure system which based on men’s perspective. Though peasant women seem invisible in the land reform struggle, they are actively making choices and decisions from ‘behind the stage’ particularly in relation to their own land cultivation. Activating their multiple identities –e.g. as women abandoned by their husbands and have to meet family needs– peasant women are able to build relationships with parties that can help them to solve their problems and achieve their objectives. This study was conducted in Blitar of East Java in March 2005. In this study, women refer to peasant women who economically abandoned by their husband and elderly widows.